Analysis of Critical Thinking Skills of Senior High School Department of Mipa on Biological Materials with Environmental Socio-Scientific Issues (ESSI) - Alpahmi Aji Satria; Sulistyo Saputro; Sutarno Sutarno; Harjana Harjana (Budapest International Research and Critics University, 2022)
This study aims to describe the critical thinking skills of students of class X MIPA SMA Negeri 1 Tiga Dihaji, SMA Negeri 1 Buay Sandang Aji, and SMA Negeri 2 Muaradua. This type of research is descriptive research with a qualitative approach. This research was carried out in class X Mathematics and Natural Sciences (N=124) students by working on the Essay test instrument for critical thinking skills on Environmental Socio-Scientific Issues (ESSI)-based biology material. The results showed that students' critical thinking skills were still very lacking, namely in the interpretation aspect 44.95% with very poor criteria, analysis aspect 40.12% with very poor criteria, 49.79% evaluation with very poor criteria, and 40.72% inference aspect with very poor criteria.